THE GLOBAL INFLUENCE OF MANGA ON MODERN SOCIETY (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article provides a detailed analysis of the global influence of manga on modern society. Manga, which originated in Japan as a form of comic art and visual storytelling, has developed into one of the most popular and economically successful cultural industries in the world. Over the past decades, manga has moved beyond national borders and gained millions of readers in Asia, Europe, North America, Latin America, and many other regions. Today, manga is not only a source of entertainment but also an important cultural phenomenon that affects social values, education, communication, fashion, tourism, and digital media.
Keywords: Manga, Japanese culture, global influence, modern society, youth culture, entertainment industry, anime, education, digital media, publishing.